1990
DOI: 10.1172/jci114635
|View full text |Cite
|
Sign up to set email alerts
|

Expression of functional interleukin 2 receptors by peripheral blood monocytes from patients with active pulmonary tuberculosis.

Abstract: Peripheral blood monocytes from patients with active

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
2

Year Published

1991
1991
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 36 publications
3
34
0
2
Order By: Relevance
“…For CD25, we demonstrated that cell-surface and soluble CD25 induced by infection can function as an IL-2 scavenger receptor. This is in line with clinical evidence linking increased levels of sCD25 to immunosuppression in infectious (43)(44)(45) and malignant diseases (46,47 (26).…”
Section: Discussionsupporting
confidence: 88%
“…For CD25, we demonstrated that cell-surface and soluble CD25 induced by infection can function as an IL-2 scavenger receptor. This is in line with clinical evidence linking increased levels of sCD25 to immunosuppression in infectious (43)(44)(45) and malignant diseases (46,47 (26).…”
Section: Discussionsupporting
confidence: 88%
“…Because IL-2R was detected predominantly on T-lymphocytes after stimulation by purified protein derivative (PPD) [17], we have reason to believe that T-cells are the major source of sIL-2R in patients with active TB. However, an in vitro study has demonstrated the expression of IL-2R by peripheral blood monocytes from patients with active pulmonary TB [18]. Therefore, monocytes may contribute to the pool of circulating sIL-2R in patients with active TB.…”
Section: Discussionmentioning
confidence: 99%
“…The demonstration of M. tuberculosis in the peripheral blood of animals, demonstrated after inoculation and culture [23], led us to investigate the suitability of patients' blood for detection of M. tuberculosis by PCR. Moreover, the possibility of mycobacteraemia has been suggested recently as activation of circulating human peripheral blood monocytes, which results in the expression of gene for TL-2R followed in turn by the appearence of IL-2R on the cells surface [24,25] and the increase of IL-1 production, has been demonstrated during active human tuberculosis [26]. On the basis of these considerations this new technique was applied to the detection of M. tuberculosis in peripheral blood of patients with acute tuberculosis.…”
Section: Discussionmentioning
confidence: 99%